God as an Attachment Figure: A Case Study of the God Attachment Language and God Concepts of Anxiously Attached Christian Youths in South Africa. Issue 4 (1st October 2016) - Counted, Victor
ABSTRACT: This study examines the role of the Christian God as an attachment figure, using the attachment language criteria of a strong and enduring affectionate bond. Respondents were 15 anxiously attached Christian youths, purposefully selected for in-depth interviews to explore their God attachment language and God concepts. The results show how the respondents saw God as a target for their proximity-seeking behaviors, albeit conflicted in their relationship experience. They also used some form of metaphorical theology that represented God to them as either stronger or wiser, as a safe haven for security, or as a response to their internal conflict.